The The Effectiveness Of Project Based Learning Learning Model Based On Local Wisdom Plantae Material To Improve Students' Science Literacy Ability (Journal of Innovative Science Education, 2022)
Scientific literacy is an ability that students must have in facing the challenges of the 21st century and is also one of the objectives of implementing the 2013 Curriculum. The object of this research is the basic competencies of Plantae material which is taught using project based learning (PjBL) based on local wisdom. This study aims to analyze the effectiveness of project-based learning (PjBL) based on local wisdom to train students' scientific literacy skills. This research was conducted in class X MA NU Miftahul Falah Dawe Kudus, the sample of this study was taken by using saturated sampling technique. This research design using One Group Pretest Posstest Design. The data was collected using test with indicators of scientific literacy competence. The test results were analyzed using the N-gain test and paired sample t-test to prove the effectiveness of the learning. The results showed that the level of learning effectiveness was moderate with the average of N-Gain 0.66. The results of the paired sample t-test obtained a value of sig. 0.0000 <Î± = 0.05, which means that there is a significant difference between the pretest and posttest mean values. Based on the research results it can be denied that the project-based learning based on local wisdom of the Plantae material is effective to train students' scientific literacy competencies